Perancangan Database Point of Sales Apotek Dengan Menerapkan Model Data Relasional - Rusydi Umar; Abdul Hadi; Panggah Widiandana; Fahmi Anwar; Muhammad Jundullah; Ahmad Ikrom (Query: Journal of Information Systems, 2019)
Database design is a process of designing data needed to support various system designs. The benefit of a database in Point of Sales drug sales in the Jogja Pharmacy enables storing, changing and returning all data quickly and easily. Problems in database design are different viewpoints from the designer, programmer and end-user. Because of that, the design is needed a methodology the process of designing a good database starting from procedures, techniques, tools and documentation. The database planning method used in Research and Development (R & D) and the database design method uses the Database Life Cycle (DBLC) variable research is POS pharmacy. Research aspects include requirement analysis, conceptual design, logical design and physical design. The final result of this research is to create 8 types of conceptual consists of drugs, drugs, customers, stores, users, detailed details, and temporary details.Keywords: database, apotek, POS, DBLC, relational data